PERMAINAN ULAR TANGGA BERBANTUAN WORDWALL SEBAGAI MEDIA INOVATIF DALAM MENINGKATKAN KETERLIBATAN SISWA SMAN 2 GUNUNG TALANG SOLOK - Desy Eka Muliani; Yusmanila; Yeni Nurpatri; Zaturrahmi; Ilham Adi Putra; Jesica Riby; Desmawati; Lela Sefita Sari (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to enhance students’ interest and understanding in learning Physics through the implementation of the Snakes and Ladders educational game integrated with the Wordwall platform. The target participants were 10th-grade students at SMAN 2 Gunung Talang, Solok Regency, West Sumatra. The implementation stages included the preparation of interactive learning media, teacher training on media usage, classroom implementation, and evaluation through learning outcome tests and student response questionnaires. The results showed that the application of the Snakes and Ladders game assisted by Wordwall successfully increased students’ active engagement during lessons, created a joyful learning atmosphere, and facilitated better comprehension of Physics concepts. Moreover, both students and teachers expressed high levels of satisfaction with this innovative approach. This program recommends the integrated use of digital and analog game-based media as an alternative active learning strategy in secondary schools.